Correlation of Nutritional Status Bades on Upper Arm Circumference (LiLa) of Pregnant Woment with Low Birth Weight Infants (LBW) - Ariyani Lutfitasari; Lia Mulyanti; Umi Khasanah (Jurnal Kebidanan, 2023)
Poor nutritional status of pregnant women is associated with adverse births including intrauterine growth disorders and low birth weight (LBW), which have a detrimental impact on the development of their lives. The purpose of this study was to find out about the relationship between upper arm circumference (LiLa) in pregnant women and low birth weight babies. This type of research is a type of quantitative analytic study using a cross-sectional design, by taking a sample with a total sample. The results of the research on the nutritional status of pregnant women showed that 35 respondents (34.3%) experienced CED and 67 respondents (65.7%) did not experience CED, 30 respondents had LBW babies (29.4%) and 72 respondents did not have LBW (70.6%). The relationship between the nutritional status of pregnant women and the incidence of LBW was found that most of the respondents who experienced CED had babies who were LBW, namely 16 respondents (45.7%) and the respondents who did not experience CED were mostly not gave birth to LBW babies, namely as many as 53 respondents (79.1%). The conclusion is that there is a relationship between the nutritional status of pregnant women based on Lila and the incidence of LBW at the Bangetayu Health Center, Semarang City.